Impacts of the COVID-19 pandemic on the experiences of incarcerated pregnant people - L. Noël Marsh; Camille Kramer; Rebecca J. Shlafer; Carolyn B. Sufrin (BMC, 2024)
Abstract Background The COVID-19 pandemic disproportionately impacted incarcerated populations, yet few studies have investigated the specific effects on incarcerated pregnant people. This study compares pregnant people's experiences of pregnancy and parenting in prison before and during the pandemic in order to explore the impacts of COVID-19 on this population. Methods We conducted semi-structured interviews with pregnant people at a state prison as part of a larger study on pregnant people's experiences during incarceration. Interviews explored participants' experiences and decision-making related to pregnancy and parenting while incarcerated. This secondary analysis compared interviews conducted between June 2019 and March 2020 (pre-COVID-19) to interviews conducted between June and November 2020 (during COVID-19). Interviews conducted during the pandemic included questions about the impact of COVID-19 on participants' experiences. Brief three and six-month follow-up interviews were conducted when possible. Results COVID-19 introduced new stressors and exacerbated preexisting stressors around participants' reproductive and parenting experiences. Three major themes emerged: 1) incarceration causes mental, emotional, and physical distress during pregnancy and parenting; 2) COVID-19 worsened conditions of incarceration, contributing to participants' distress; and 3) the introduction of quarantine protocols during the pandemic felt uniquely punitive for pregnant and postpartum people. Conclusions The COVID-19 pandemic was characterized as a major crisis and primary threat to public health, particularly for incarcerated individuals. Yet just as COVID-19 exacerbated preexisting disparities for marginalized, non-incarcerated communities, incarcerated pregnant people similarly described a "worsening" of already-intolerable conditions. The indiscriminate application of quarantine protocols for pregnant people reflects broader carceral logics of control that do not account for the wellbeing of pregnant and postpartum people and their infants, as evidenced by current practices of infant separation, a lack of support, and physically taxing living conditions.